Determining the Phytochemical Parameters of Pisum sativum (pease) and Effects on the Development of Debaryomyces hansenil - Erecevit, Pinar; Kirbag, Sevda (Assoc Pharmaceutical Teachers India, 2017)
Objective: In this work; phytochemical parameters (fatty acid, vitamin, phytosterol, flavonoid and resveratrol contents, and antioxidant activities antimicrobial activities) of Pisum sativum (pease) extracts prepared with Debaryomyces hansenii were detected. P. sativum (pease) is known as one of the nutritional sources of prebiotics. Methods: Phytochemical contents of extracts were evaluated with device and assays like Shimadzu 17, Shimadzu brand HPLC, Spectrophotometer device and well agar methods respectively. Results: it was observed that total fatty acid, flavonoid, contents in pease extracts were at low levels and vitamin, and phytosterol contents were at changing. It was detected that total fatty acid, vitamin and phytosterol contents; at significant rates of pease extracts prepared with D. hansenii; however, flavonoid contents decreased at different rates. In the work, it was noticed that pease had increasingly antioxidant activities and antimicrobial activities at changing rates, acordingly at fatty acid, vitamin and phytosterol levels; at significant rates increased. On the other hand, flavonoid extracts demonstrated scarcely any antimicrobial activity. When antimicrobial activities of pease extracts containing D. hansenii were analyzed, they had effect at increasing rates of fatty acid, vitamin and phytosterol. On the other hand, it was demonstrated that flavonoid extracts did not have any antimicrobial activity against all of the microorganisms except Bacillus megaterium DSM 32. Conclusion: it was detected that pease which is known as prebiotic food, can be used in terms of proper prebiotic and the relationship of proper prebiotic-prebiotic (symbiotic) for the development of D. hansenii used in this study which is also accepted as probiotic yeast. It was observed that this yeast type developing in extracts obtained from pease affected other beneficial nutrients such as vitamins, minerals, phenolic compounds at varying rates.
Keywords: Debaryomyces hansenii; Pisum sativum (pease); Symbiotic; Phenolic compounds